IF-AHP method: A decision-making tool for personnel selection / Che Siti Zaiznena Che Mat Zain ... [et al.] - Che Mat Zain, Che Siti Zaiznena; Mohd Syahidan, Saffiya Nuralisa; Saidin, Nur Qamarina Hanim; Mahad, Nor Faradilah (2022)
This project focuses on the Intuitionistic Fuzzy Analytic Hierarchy Process (IF-AHP) method in solving personnel selection problems for any available position in a company instead of the traditional method of choosing new personnel. This is the novelty of the project. The objective of this project is to implement the IF-AHP method as a powerful tool in solving new personnel selection for a position in a company. The IF-AHP method is simple in computations and cost-effective since the analysis can be done using MS Excel. The IF-AHP method is executed to solve selection problems because it can handle hesitancy, ambiguity, and intuition judgments made by decision-makers (DMs) and increase the accuracy of the assessment. This mathematical model can be assigned to any area of Multi-Criteria Decision Making (MCDM) problems as portfolio selection and for best student selection that considers multiple conflicting criteria.